The Complete Letters of Henry James, 1884-1886 Volume 2. - James, Henry (Nebraska, 2021)
This fifteenth installment in the complete collection of Henry James's more than ten thousand letters records James's ongoing efforts to care for his sister, develop his work, strengthen his professional status, build friendships, and engage timely political and economic issues.
Description based upon print version of record.
June 13 To William James.
Keywords: James, Henry, -- 1843-1916 -- Correspondence.; James, Henry, -- 1843-1916; Authors, American -- 20th century -- Correspondence.; Authors, American -- 19th century -- Correspondence.; Écrivains américains -- 20e siècle -- Correspondance.; Écrivains américains -- 19e siècle -- Correspondance.; Authors, American; 1800-1999; Personal correspondence